P96 A survey for children/young people supported by a hospice. (1st October 2013) - Stanford, Jo; Phillips, Ruth
Abstract : A survey for children/young people supported by a hospice Introduction: The Care Quality Commission requires agencies to enable services users to participate in the development of the service. Aims: This survey represents a children's hospice first attempt to hear directly from the children and young people they support as part of the organisations Clinical Governance process. Methods: Children and young people using hospice services have a wide range of needs, abilities and disabilities. Participants were encouraged to complete the surveys on their own if able or if needed with help from their siblings or parents/carers. The format was a simple questionnaire provided on paper and accessible on-line to offer participants a choice about how to reply. Completed paper surveys were added to the on-line programme manually by the Clinical Governance Facilitators to aid collation and analysis. Results: Of the 438 forms sent out 67 (15%) were retuned; some completed by the child/young person, on their behalf by siblings or parent/carer or siblings from their own perspective. Respondents commented on activities they would like to see offered by the hospice such as DJ evenings and outings including holidays abroad. They also highlighted a few things they didn't like such as staying over at the same time as young children. Discussion: The survey offered children and young people with a range of complex needs the opportunity to comment on their experiences. The results will be shared with staff so they can discuss and consider ways of implementing changes to their practice in an effort to meet specific needs and improve the experiences of the service users. Conclusion: The survey has provided a starting point. In future we plan to review the survey and include other methods such as participant observation to offer more children and young people the chance to participate.